Integration of smart water management and photovoltaic pumping system to supply domestic water for rural communities - Meita Rumbayan; Imanuel Pundoko; Sherwin R．U Sompie; Dirko G．S Ruindungan (Results in Engineering)
Water scarcity continues to pose a significant challenge for rural communities globally, compounded by inadequate access to dependable energy sources and water management systems. This research introduces a novel method that combines smart water management technologies with a photovoltaic pumping system to provide a sustainable domestic water supply to rural areas. The system utilizes solar energy captured by photovoltaic panels, which is stored and regulated through an efficient charge controller and battery configuration to power water pumps. Centralized control is facilitated by an ESP32 microcontroller, which processes real-time data from various sensors monitoring water flow, levels, voltage, and current. This setup enables precise control and energy-efficient water distribution, optimizing resources and ensuring consistent water availability. This approach not only signifies a significant advancement in sustainable rural water management but also offers a scalable solution adaptable to various environmental conditions. By integrating renewable energy and smart technology, this system paves the way for enhanced self-sufficiency and environmental stewardship for underserved populations.